Creativity in local government: Definition and determinants. (17th July 2017) - Kruyen, Peter M.; van Genugten, Marieke
Abstract: In current thinking about public service improvement, civil servant creativity plays an important role. Using the results of 43 semi‐structured interviews, we assessed the degree to which our theoretical knowledge about creativity—based primarily on business research—matches the insights of managers in local government. Respondents considered employee creativity to be important, but—in contrast to the literature—understood creativity as the act of trying out new things to better deal with specific problems at hand instead of developing new ideas potentially applicable to a wider context. As such, respondents did not see creativity as the main precondition for innovation. In line with the literature, there is little consistency across respondents about individual‐ and context‐level determinants of creativity. Lastly, respondents put forward several factors that have received little attention in the literature but are particularly relevant in understanding differences in work‐related creativity in the context of local government.